2007
DOI: 10.1590/s0102-261x2007000600007
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in mesospheric gravity wave studies using nigthglow imaging system

Abstract: ABSTRACT.A variety of optical remote sensing techniques have now revealed a rich spectrum of wave activity in the upper atmosphere. Many of these perturbations, with periodicities ranging from ∼5 min to many hours and horizontal scales of a few tens of km to several thousands km, are due to freely propagating atmospheric gravity waves and forced tidal oscillations. Passive optical observations of the spatial and temporal characteristics of these waves in the mesosphere and lower thermosphere (MLT) region (∼80-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The generated gravity waves can propagate upward and can modulate the airglow layers in the 80-100 km height range [Taylor and Hapgood, 1988;Taylor et al, 2007;Snively and Pasko, 2008]. Using the imaging nighttime airglow from ground observation sites [Taylor and Hapgood, 1988;Swenson and Mende, 1994;Chung et al, 2003;Sentman et al, 2003;Taylor et al, 2007;Suzuki et al, 2013;Xu et al, 2015] or spaceborne observation [Dewan et al, 1998;Mende et al, 1998;Yue et al, 2013;Akiya et al, 2014;Xu et al, 2015], gravity waves can be easily identified and observed. In addition, storm-generated gravity waves have also been confirmed by GPS data [Horinouchi and Tsuda, 2009;Lay et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…The generated gravity waves can propagate upward and can modulate the airglow layers in the 80-100 km height range [Taylor and Hapgood, 1988;Taylor et al, 2007;Snively and Pasko, 2008]. Using the imaging nighttime airglow from ground observation sites [Taylor and Hapgood, 1988;Swenson and Mende, 1994;Chung et al, 2003;Sentman et al, 2003;Taylor et al, 2007;Suzuki et al, 2013;Xu et al, 2015] or spaceborne observation [Dewan et al, 1998;Mende et al, 1998;Yue et al, 2013;Akiya et al, 2014;Xu et al, 2015], gravity waves can be easily identified and observed. In addition, storm-generated gravity waves have also been confirmed by GPS data [Horinouchi and Tsuda, 2009;Lay et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Most frequently the filters J, H, and K are used to isolate the wavelength regions 1.165-1.328 µm, 1.484-1.780 µm, and 2.083-2.363 µm, respectively. The J-band filter spans two OH Meinel transitions, the (7,4) and (8,5), while the H-band filter contains the (3,1), (4,2), (5,3) and (6,4) transitions and the K-band filter spans the (9,7) transition.…”
Section: Instrumentation and Data Setmentioning
confidence: 99%
“…Radiative relaxation of this excited OH in the Meinel system results in the bright near-infrared (NIR) radiation known as OH nightglow or airglow. The OH Meinel emission occurs over an approximately 8 km thick layer [1], and spectroscopic observations of the nightglow have been used to infer the atmospheric conditions at the peak of the layer near 87 km altitude [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydroxyl (OH) airglow near 90 km (Meinel, , ) is one of the more intense emissions, and observations of the OH airglow are often employed to measure gravity waves and breaking features in the MLT region (Diettrich et al, ; Fritts et al, ; Li et al, ). Responding to a wide range of vertical wavelengths (Liu & Swenson, ; Swenson & Gardner, ), measurements of the horizontal wavelength of gravity waves have been made with OH airglow imagers (Sedlak et al, ; Taylor et al, ). Studies such as these typically detected atmospheric gravity waves in the OH airglow layer on scales of the order ~1 to hundreds of kilometers.…”
Section: Introductionmentioning
confidence: 99%